2016
DOI: 10.1038/cgt.2016.30
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of angiopoietin 2 promotes the formation of oral squamous cell carcinoma by increasing epithelial–mesenchymal transition-induced angiogenesis

Abstract: Oral squamous cell carcinoma (OSCC) is the most common cancer of the head and neck and is associated with a high rate of lymph node metastasis. The initial step in the metastasis and transition of tumors is epithelial–mesenchymal transition (EMT)-induced angiogenesis, which can be mediated by angiopoietin 2 (ANG2), a key regulatory factor in angiogenesis. In the present study, immunohistochemistry and real-time quantitative reverse transcriptase (qRT-PCR) were used to measure the expression of ANG2 in OSCC tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 24 publications
2
18
0
1
Order By: Relevance
“…RNA interference: new mechanistic and biochemical insights would present a reduction in their capacity to invade and migrate through the EMT process. 90 The same pattern was observed in the case of siRNA inhibition of superoxide dismutase 2 in SACC-LM that led to E-cadherin increased levels as well as the decreased expression of migration-associated genes Vimentin, Slug, Snail, p-ERK, and MMP-2. 91 Aberrant Notch4 expression has an essential function in OSCC tumorigenesis and promotes metastasis by perineural spread, 92 becoming an important prognosis marker and therapeutic target.…”
supporting
confidence: 57%
“…RNA interference: new mechanistic and biochemical insights would present a reduction in their capacity to invade and migrate through the EMT process. 90 The same pattern was observed in the case of siRNA inhibition of superoxide dismutase 2 in SACC-LM that led to E-cadherin increased levels as well as the decreased expression of migration-associated genes Vimentin, Slug, Snail, p-ERK, and MMP-2. 91 Aberrant Notch4 expression has an essential function in OSCC tumorigenesis and promotes metastasis by perineural spread, 92 becoming an important prognosis marker and therapeutic target.…”
supporting
confidence: 57%
“…Angiopoietin-2 caninduce anarchical blood vessel organization during cancer progression and enhance the effect of vascular endothelial growth factor during active neovascularization (38,39). Additionally, angiopoietin-2 serves a notable role in the migration and invasion of a malignancy, and is partly responsible for inducing abnormal epithelial-mesenchymal transition (40). Upregulation of angiopoietin-2 expression was observed in diverse human malignant tumors, but notable expression does not occur in healthy individuals, meaning it may represent a novel mechanistically directed target for antitumor therapy.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 The expression of angiopoietin-2 is upregulated at sites of tumor angiogenesis in multiple types of cancer, and overexpression of angiopoietin-2 promoted angiogenesis and tumor growth in experimental models. 8,29,30 Importantly, overexpression of angiopoietin 2 accelerated the carcinogenesis of oral squamous cell carcinoma through promoting epithelial-mesenchymal transition-induced angiogenesis. 8 Angiopoietin-2 has been proposed as a potential target for antiangiogenic drug development.…”
Section: Discussionmentioning
confidence: 99%
“…6 Animal study reported that overexpression of angiopoietin-2 has also been shown to promote the growth and metastasis of oral SCC. 8 Besides, experimental study demonstrated the distinct expressions of angiopoietin-1 and angiopoietin-2 in tumor samples of human oral SCC. 9 However, the dynamic changes of these angiogenic factors in the setting of tumor resection remains unclear.…”
Section: Introductionmentioning
confidence: 97%